STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA DI LEMBAGA PENDIDIKAN ISLAM - Annisa Judithya Ayu Nur Affandy; Barokah Isdaryanti; Joko Sutarto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Human resource (HR) development is a key element in improving the standards of Islamic educational institutions in the era of globalization and the industrial revolution 4.0. This study applies library research methods by analyzing literature related to HR development strategies in Islamic educational institutions. The results show that HR development can be carried out through training, mentorship programs, welfare improvements, performance evaluations, spiritual development, technology utilization, collaboration, and innovation. The implementation of these strategies plays a crucial role in improving the quality of human resources, thus preparing them to face the demands and challenges of Islamic education in the future.